Looking back: Kautz Gyula College of Economics - Stion, Zsuzsa; Kovács, Gábor (Tér - Gazdaság - Ember/Journal of Region, Economy and Society, 2023)
The Kautz Gyula College of Economics is the intellectual center and workshop of the Kautz Gyula Faculty of Economics, whose main mission is to provide elite education and build an outstanding academic, professional, and human community. We took over the management of the Gyula Kautz College of Economics in the fall of 2013 and served as program director and teacher until early 2017. Getting involved in the work of the college, which was founded in 1997, was a great challenge and task, as it was an organization with a large membership in terms of colleges, a complex operational structure, and scientific, professional, and community-building events. We will proceed with this retrospective and recollection of memories according to the criteria listed above.